2020
DOI: 10.1159/000511082
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Grade 4–5 Chronic Kidney Disease Patients

Abstract: <b><i>Introduction:</i></b> Chronic kidney disease (CKD) increases the risk of mortality during coronavirus disease 2019 (COVID-19) episodes, and some reports have underlined the high incidence and severity of this infection in dialysis patients. Information on COVID-19 in nondialysis CKD patients is not available yet. <b><i>Case Reports:</i></b> Here we present 7 patients with grade 4–5 CKD who developed symptomatic COVID-19; they comprise 2.6% of our 267 advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
4
13
0
1
Order By: Relevance
“… 14 A study by Collado et al showed that COVID‐19 infected patients with advanced CKD with or without AKI had a tendency to present with more respiratory symptoms like cough and dyspnoea. 10 This was similar to our findings. The prevalence of cardiovascular disease among patients with KD could worsen fluid overload and lead to exacerbation of respiratory symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 14 A study by Collado et al showed that COVID‐19 infected patients with advanced CKD with or without AKI had a tendency to present with more respiratory symptoms like cough and dyspnoea. 10 This was similar to our findings. The prevalence of cardiovascular disease among patients with KD could worsen fluid overload and lead to exacerbation of respiratory symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…ERA‐EDTA council and ERACODA working group highlighted that dialysis (3.7×), organ transplant (3.5×) and advanced CKD (2.5×) were three of the top four risk factors associated with COVID‐19 deaths 14 . A study by Collado et al showed that COVID‐19 infected patients with advanced CKD with or without AKI had a tendency to present with more respiratory symptoms like cough and dyspnoea 10 . This was similar to our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Collado et al . [ 19 ] presented a case series with seven patients suffering from CKD in which the Estimated Glomerular filtration rate (eGFR) was between 12 and 20 mL/min during the month prior to the COVID-19/SARS-COV-2 infection. The three major symptoms were fever, cough and dyspnoea, and five patients showed bilateral pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to a study by Collado et al, which showed that the presenting complaints among the patients with CKD were fever, breathlessness, and cough. The inflammatory parameters were also similar among patients with CKD [ 13 ].…”
Section: Discussionmentioning
confidence: 99%